Comprehensive Genomic Characterization Analysis of lncRNAs in Cells With Porcine Delta Coronavirus Infection - Liu, Junli; Wang, Fangfang; Du, Liuyang; Li, Juan; Yu, Tianqi; Jin, Yulan; Yan, Yan; Zhou, Jiyong; Gu, Jinyan (Frontiers in Microbiology, 2020)
Porcine delta coronavirus (PDCoV) is a novel emerging enterocyte-tropic virus with diarrhea, vomiting, dehydration and mortality in suckling piglets. Long noncoding RNAs (lncRNAs) are identified as important regulators during virus infection. Here, we describe a comprehensive transcriptome profile of lncRNA alterations in PDCoV infected ST cells. Totally, 1308 annotated and 1190 novel lncRNA candidates were identified. The Gene Ontology and Kyoto Encyclopaedia of Genes and Genomes (KEGG) analysis of whole genome-wide lncRNAs revealed lncRNAs might be involved in numerous biological processes. SNP and indel analysis in lncRNAs loci identified nine genes that contains seventeen SNPs. Clustering analysis of differentially expressed lncRNAs showed 454 novel and 276 annotated lncRNAs altered after PDCoV infection. Furthermore, we constructed lncRNAs-protein-coding genes co-expression interaction networks. The KEGG analysis of the co-expressed genes showed that these differentially expressed lncRNA were enriched in pathways related to metabolic pathway and TNF signaling pathway. Our study provided a rich lncRNAs information for exploring pathogenesis and antiviral therapy of PDCoV infection.